Producers and consumers split over banana trade - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Single European Market brings new controls on banana imports Bananas come third, after coffee and tea, in the league table of foodstuffs traded worldwide. Production methods vary as widely as the marketing regulations from continent to continent....